Disclosure of public-private partnership (PPP) voluntary information: case of Malaysian PPP projects - Musawa, Mubarak Shehu; Ismail, Suhaiza; Ahmad @ Abdul Mutalib, Hawa (Emerald Group Publishing Ltd., 2017)
Purpose – The purpose of this paper is twofold: first, it seeks the perception of public-private partnership (PPP) experts on the importance of desirable PPP information that can be voluntarily reported by the private sector; and second, it determines the extent and quality of voluntary disclosure of PPP information by private entities.